Perspectives on Conservation Impacts of the Global Primate Trade - Gal Badihi; Daniel R. K. Nielsen; Paul A. Garber; Mike Gill; Lisa Jones-Engel; Angela M. Maldonado; Kerry M. Dore; Jennifer D. Cramer; Susan Lappan; Francine Dolins; Emerson Y. Sy; Agustin Fuentes; et al. (International Journal of Primatology, 2024)
The global trade in nonhuman primates represents a substantial threat to ecosystem health, human health, and primate conservation worldwide. Most of the primate trade involves trade for pet-keeping, consumption, or biomedical experimentation. We present an overview of international primate trade through five case studies; each describes a different facet of this trade. We draw on published scientific literature, media outlets, and open access datasets, including the CITES Trade Database to build these case studies. Case study 1 describes the role of introduced island populations of Macaca and Chlorocebus in trade for biomedical experimentation; case study 2 covers the global health threats posed by the primate trade, including zoonotic disease transmission once animals enter the trade pipeline; case study 3 addresses the ways that changing patterns of primate trade, from local markets to online, have increased the demand for primates as pets; case study 4 recognizes the role that local environmental activism can play in mitigating trade; and case study 5 shows variation between global regions in their contribution to the primate trade. We recommend greater oversight of primate trade, especially domestic trade within primate range countries, and real-time reporting to CITES to accurately track primate trade. Effective conservation-focused regulations that can minimise the negative effects of primate trade must be tailored to specific regions and species and require transparency, careful regulation, field research, and an understanding of the magnitude of this trade.

Rising Together in Response to the COVID-19 Pandemic - Keri Kaczor; Rosanna Alegado; Katy Hintzen; Lauren Ching; Michael Lieberman; Sandra Chang; Eileen Nakano; Angela Sy; David Horio; Kaeo Tam; Vivek Nerurkar; Ashley Smyth; et al. (Oceanography, 2024)
The COVID-19 pandemic created a socioeconomic shock that heavily impacted coastal and Great Lakes communities. In response, the NOAA National Sea Grant Program tailored efforts to meet local and regional needs, with an emphasis on research, extension, and education. This paper presents an overview of four projects that illustrate Sea Grant’s priorities in action and how Sea Grant was able to respond collaboratively to the pressing needs of coastal communities and economies during the COVID-19 pandemic. The case studies also demonstrate how Sea Grant provides expertise to protect and restore coastal ecosystems, supports resilient communities and economies, promotes sustainable fisheries and aquaculture, enables an environmentally literate public, and bolsters a skilled workforce that serves the needs of coastal communities and ecosystems. They also demonstrate how these experiences made coastal communities and Sea Grant more resilient to unexpected disruptions in the long term, and how these efforts shaped Sea Grant and who it serves in times of crisis and beyond.

Results of the George Washington University cancer center’s comprehensive cancer control cancer communication mentorship program and implications for future practice - Dao Duong; Danielle Agraviador; Charlene Cariou; Maria George; Miriam Karanja; Kanako Kashima; Sarah Kerch; Mohammad Khalaf; Brad Love; Lauren McCauley-Hixenbaugh; Serena Phillips; Susana Ramirez; et al. (Cancer Causes & Control, 2022)

Evaluating the implementation of cervical cancer screening programs in low-resource settings globally: a systematized review - J. Andrew Dykens; Jennifer S. Smith; Margaret Demment; E. Marshall; Tina Schuh; Karen Peters; Tracy Irwin; Scott McIntosh; Angela Sy; Timothy Dye (Cancer Causes & Control, 2020)
Purpose Cervical cancer disproportionately burdens low-resource populations where access to quality screening services is limited. A greater understanding of sustainable approaches to implement cervical cancer screening services is needed. Methods We conducted a systematized literature review of evaluations from cervical cancer screening programs implemented in resource-limited settings globally that included a formal evaluation and intention of program sustainment over time. We categorized the included studies using the continuum of implementation research framework which categorizes studies progressively from “implementation light” to more implementation intensive. Results Fifty-one of 13,330 initially identified papers were reviewed with most study sites in low-resource settings of middle-income countries (94.1%) ,while 9.8% were in low-income countries. Across all studies, visual inspection of the cervix with acetic acid (58.8%) was the most prevalent screening method followed by cytology testing (39.2%). Demand-side (client and community) considerations were reported in 86.3% of the articles, while 68.6% focused scientific inquiry on the supply side (health service). Eighteen articles (35.3%) were categorized as “Informing Scale-up” along the continuum of implementation research. Conclusions The number of cervical cancer screening implementation reports is limited globally, especially in low-income countries. The 18 papers we classified as Informing Scale-up provide critical insights for developing programs relevant to implementation outcomes. We recommend that program managers report lessons learnt to build collective implementation knowledge for cervical cancer screening services, globally.